2014
DOI: 10.4103/1817-1737.140132
|View full text |Cite
|
Sign up to set email alerts
|

Association of compliance of ventilator bundle with incidence of ventilator-associated pneumonia and ventilator utilization among critical patients over 4 years

Abstract: BACKGROUND:Several studies showed that the implementation of the Institute for Healthcare Improvement (IHI) ventilator bundle alone or with other preventive measures are associated with reducing Ventilator-Associated Pneumonia (VAP) rates. However, the association with ventilator utilization was rarely examined and the findings were conflicting. The objectives were to validate the bundle association with VAP rate in a traditionally high VAP environment and to examine its association with ventilator utilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 28 publications
(40 reference statements)
1
21
0
5
Order By: Relevance
“…In one of the studies, the patients diagnosed by BAL had a lower number of confirmed VAP (6.1 vs. 25.5/1000 ventilation days) compared to those diagnosed with non-protective aspiration, which was characterised by 90% sensitivity and only 14% specificity [24]. The literature data indicate that VAP prophylaxis, in the form of the ventilation bundle, can result in notable effects, i.e., decreased incidence [3,15,23,25]; however, studies confirming the lack of infections of this type in a given period are sparse [17,26]. Moreover, the complete elimination of VAP has been questioned [27].…”
Section: Discussionmentioning
confidence: 99%
“…In one of the studies, the patients diagnosed by BAL had a lower number of confirmed VAP (6.1 vs. 25.5/1000 ventilation days) compared to those diagnosed with non-protective aspiration, which was characterised by 90% sensitivity and only 14% specificity [24]. The literature data indicate that VAP prophylaxis, in the form of the ventilation bundle, can result in notable effects, i.e., decreased incidence [3,15,23,25]; however, studies confirming the lack of infections of this type in a given period are sparse [17,26]. Moreover, the complete elimination of VAP has been questioned [27].…”
Section: Discussionmentioning
confidence: 99%
“…The increment of overall compliance for VAP preventative strategies as found in the prospective study versus the retrospective study mimics the findings of several other VAP studies (Al-Thaqafy, El-Saed, Arabi, & Balkhy, 2014;Babcock et al, 2004;Bigham et al, 2009;Bouadma, Mourvillier, Deiler, Le Corre, et al, 2010;Brierley et al, 2012;Lawrence & Fulbrook, 2012). Interestingly, differences between individual VAP preventative strategies reported in the retrospective versus the prospective study were statistically significant (oral hygiene, HOB elevation, cuff pressure and ventilator checks).…”
Section: Discussion Of Vap Preventative Strategies Complianceretrospesupporting
confidence: 82%
“…[42434445464748] All these studies were based on pre- and post-intervention observational designs except for two, which were prospective cohort studies. [4244] The total number of patient ventilator days was 64,414, with the highest number (41,034) reported by Al-Dorzi et al . [42] Cost estimates were mentioned in two studies: Bukhari et al .…”
Section: Initiatives For Improving Ventilator Care In the Kingdom Of mentioning
confidence: 99%
“…However, some organizations introduced other prevention measures. Four of the seven institutions added oral care with chlorhexidine,[43444748] two implemented the use of endotracheal tubes with subglottic secretion drainage,[4348] and one monitored endotracheal tube cuff pressure. [43] The overall bundle compliance improved from 48.6% to 94.3% (an increase of 49%), with Al-Tawfiq and Abed[46] reporting the greatest improvement (75.6%).…”
Section: Initiatives For Improving Ventilator Care In the Kingdom Of mentioning
confidence: 99%
See 1 more Smart Citation